Elevated free fatty acids affect bovine granulosa cell function: a molecular cue for compromised reproduction during negative energy balance. Issue 5 (May 2019) - Sharma, Arpna; Baddela, Vijay Simha; Becker, Frank; Dannenberger, Dirk; Viergutz, Torsten; Vanselow, Jens
Abstract : High-yielding dairy cows postpartum face the challenge of negative energy balance leading to elevated free fatty acids levels in the serum and follicular fluid thus affecting the ovarian function. Here, we investigated effects of physiological concentrations of palmitic acid (PA), stearic acid (SA) and oleic acid (OA) on the viability, steroid production and gene expression in a bovine granulosa cell (GC) culture model. Treatment with individual and combined fatty acids increased the CD36 gene expression, while no significant apoptotic effects were observed. Both PA and SA significantly upregulated the expression of FSHR, LHCGR, CYP19A1, HSD3B1, CCND2 and increased 17β-estradiol (E2) production, while OA downregulated the expression of these genes and reduced E2. Interestingly, STAR was equally downregulated by all fatty acids and combination treatment. E2 was significantly reduced after combination treatment. To validate the effects of OA, in vivo growing dominant follicles (10–19 mm) were injected with bovine serum albumin (BSA) with/without conjugated OA. The follicular fluid was recovered 48 h post injection. As in our in vitro model, OA significantly reduced intrafollicular E2 concentrations. In addition, expression of CD36 was significantly up- and that of CYP19A1 and STAR significantly downregulated in antral GC recovered from aspirated follicles. The ovulation rates of OA-injected follicles tended to be reduced. Our results indicate that elevated free fatty acid concentrations specifically target functional key genes in GC both in vitro and in vivo . Suggestively, this could be a possible mechanism through which elevated free fatty acids affect folliculogenesis in dairy cows postpartum.